Resin composition for lamp member, lamp member, and method for producing resin composition for lamp member

The resin composition for lamp members, combining aromatic polysulfone with metal oxides, peroxides, or carbonates, addresses the issue of cloudiness in lamp components by enhancing heat resistance and maintaining transparency under high heat conditions, suitable for vehicle lighting applications.

JP7624396B2Active Publication Date: 2025-01-30SUMITOMO CHEM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021551222
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-02
Filing Date
2020-09-28
Publication Date
2025-01-30
Estimated Expiration
2040-09-28

AI Technical Summary

Technical Problem

Existing lamp materials, such as polyetherimide, suffer from cloudiness when exposed to high heat from light sources due to the release of volatile ingredients, which affects the transparency and performance of lamp components.

Method used

A resin composition for lamp members is developed using aromatic polysulfone combined with metal oxides, peroxides, or carbonates from the long-periodic table, which reduces cloudiness and enhances heat resistance.

Benefits of technology

The resin composition maintains excellent heat resistance and prevents cloudiness in lamp components, suitable for molding materials in various lighting applications, including headlamps and other vehicle lights.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624396000004
    Figure 0007624396000004
  • Figure 0007624396000005
    Figure 0007624396000005
  • Figure 0007624396000001
    Figure 0007624396000001
Patent Text Reader

Abstract

A lamp member resin composition according to the present invention comprises: as component (P), an aromatic polysulfone; and, as component (M), at least one type of substance selected from the group consisting of oxides, peroxides, multiple oxides, and carbonates of metals belonging to groups 1 and 2 of the long-form periodic table. The present invention also pertains to a lamp member molded from the lamp member resin composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition for lamp members that is suitably used as a molding material for lamp members, a lamp member produced using the resin composition for lamp members, and a method for producing the resin composition for lamp members. This application claims priority based on Japanese Patent Application No. 2019-182112, filed on October 2, 2019, the contents of which are incorporated herein by reference. [Background technology]

[0002] At present, polyetherimide is the mainstream material used for lamp members for automobiles and the like. For example, Patent Document 1 discloses a reflector for various lighting fixtures, including headlamps for automobiles, whose reflective surface is made of a polyetherimide resin containing 0 to 10 parts by weight of glass fiber or inorganic filler. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2004-45883 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, even polyetherimide does not have sufficient heat resistance, and there is a demand for the development of a material that has excellent heat resistance properties and can be used as an alternative to polyetherimide. As a result of investigations by the present inventors, it was found that aromatic polysulfone, which has a higher glass transition temperature and excellent heat resistance than polyetherimide, is a useful material for lamp components.

[0005] However, when the aromatic polysulfone is applied to lamp components exposed to high heat emitted from a light source, there is a problem that the lamp becomes cloudy.

[0006] The present invention has been made in order to solve the above-mentioned problems, and has an object to provide a lamp component that has excellent heat resistance and reduces the occurrence of fogging in the lamp, and a resin composition for lamp components that can be suitably used for molding the lamp component. [Means for solving the problem]

[0007] As a result of intensive research aimed at solving the above problems, the present inventors have found that fogging of lamps can be reduced by using, together with aromatic polysulfone, at least one selected from the group consisting of oxides, peroxides, double oxides and carbonates of metals belonging to Group 1 or 2 of the long form periodic table, and have thus completed the present invention. That is, the present invention has the following aspects.

[0008] (1) (P) component: aromatic polysulfone, Component (M): at least one selected from the group consisting of oxides, peroxides, double oxides, and carbonates of metals belonging to Group 1 or 2 of the long-form periodic table; A resin composition for lamp members comprising: (2) The resin composition for lamp members according to (1) above, wherein the reduced viscosity of the component (P) is greater than 0.36 (dL / g) and not greater than 0.50 (dL / g). (3) The resin composition for lamp members according to (1) or (2) above, wherein the component (M) is an oxide of a metal belonging to Group 1 or Group 2 of the long form periodic table. (4) The resin composition for lamp members according to (3) above, wherein the component (M) is magnesium oxide. (5) The resin composition for lamp members according to any one of (1) to (4) above, wherein the content of the (M) component is 0.5 to 10 parts by mass per 100 parts by mass of the (P) component. (6) A lamp member molded from the resin composition for lamp members according to any one of (1) to (5) above. (7) (P) component: aromatic polysulfone, Component (M): at least one selected from the group consisting of oxides, peroxides, double oxides, and carbonates of metals belonging to Group 1 or 2 of the long-form periodic table; A method for producing a resin composition for lamp members, comprising the step of mixing: Effect of the Invention

[0009] According to the present invention, it is possible to provide a lamp component which has excellent heat resistance and reduces the occurrence of fogging in the lamp, and a resin composition for a lamp component which can be suitably used for molding the lamp component. [Brief description of the drawings]

[0010] [Figure 1] 2A and 2B are schematic diagrams illustrating an example of a configuration of a ramp member according to an embodiment. [Diagram 2] 4 is a graph showing the results of measuring the apparent melt viscosity of the resin compositions for lamp members obtained in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the resin composition for lamp members, the lamp member, and the method for producing the resin composition for lamp members of the present invention will be described.

[0012] <Resin composition for lamp components> The resin composition for lamp components of the embodiment contains component (P): aromatic polysulfone, and component (M): at least one selected from the group consisting of oxides, peroxides, double oxides, and carbonates of metals belonging to Group 1 or 2 of the long form periodic table.

[0013] <Lamp components> The lamp member of the embodiment can be molded from the resin composition for lamp members. An example of a lamp including the lamp member of the embodiment is one that includes a light source that emits light and heat when lit, and a lamp member that surrounds the light source.

[0014] Examples of the types of light source include a light emitting diode (LED), a halogen lamp, and an HID lamp.

[0015] A lamp including the lamp member according to the embodiment can be mounted and used in vehicles such as automobiles, motorcycles, bicycles, trains, etc. One type of lamp is, for example, a headlamp. Current headlamps are broadly divided into two types: projector type and reflector type, and the resin composition for lamp members according to the embodiment can be applied to both types.

[0016] 1, an example of a projector-type lamp having the above configuration is a lamp 1 having a light source 12 and a lamp member 3. Examples of the lamp member 3 include a lens 14 that collects light emitted from the light source, a reflector 10 that reflects the light emitted from the light source 12, and a lens holder 20 that fixes the lens 14.

[0017] The lamp member of the embodiment may further include a housing that houses a light source, a reflector, a lens, etc., and a lens cover that covers the front surface of the lens and transmits light emitted from the light source.

[0018] The lamp member can be produced by using the resin composition for lamp members of the embodiment as a molding material. The problematic fogging of the lamp is believed to be due to volatile components released from the lamp member under high temperature conditions, and is presumed to be caused by substances that cause fogging adhering to the lens or lens cover. In order to increase light transmission, the lens or lens cover is often made of a material that is easily fogging, such as a transparent resin material or glass, and glass lenses are particularly prone to fogging. A lamp component molded from the resin composition for lamp components of the embodiment has excellent heat resistance and is unlikely to cause fogging of the lamp, and is therefore suitable as a component surrounding a light source that emits light and heat when lit.

[0019] The ramp member of the present embodiment is molded from the above-mentioned resin composition for ramp members. The ramp member of the present embodiment may be an article molded from the above-mentioned resin composition for ramp members.

[0020] The method for producing a ramp member may include a method having a step of molding the resin composition for a ramp member of the embodiment into a shape corresponding to the ramp member.

[0021] The molding method is preferably melt molding, and examples of the molding method include extrusion molding, T-die molding, blow molding, and injection molding. By selecting a molding method according to the shape of the component, etc., the resin composition for ramp components can be molded into a shape corresponding to the ramp component. The shape corresponding to the ramp member refers to the shape of the ramp member, the shape of a part of a portion constituting the ramp member, and the shape of the ramp member or a part thereof to which an arbitrary structure has been added.

[0022] The ramp member of this embodiment is preferably an injection molded article made from the above-mentioned resin composition.

[0023] The method for producing a ramp member may include a method having a step of injection molding the resin composition for a ramp member according to the embodiment into a shape corresponding to the ramp member. The lamp member, which is an injection molded product, can be produced by injection molding the resin composition for lamp members using a general injection molding machine at a mold temperature of 120 to 180° C. and a resin melting temperature of 330 to 400° C. Since the lamp member of the embodiment uses the resin composition for lamp members as a forming material, it has excellent heat resistance and is less likely to cause fogging of the lamp.

[0024] <(P) component> The component (P): aromatic polysulfone contained in the resin composition for lamp members will be described below. The component (P): aromatic polysulfone can be a resin having a structural unit including at least a structure in which a sulfonyl group (-SO2-), an arylene group (-Ar-), and an ether bond (-O-) are bonded in this order.

[0025] Examples of the resin include a compound represented by the following general formula (I) and a compound represented by the following general formula (II).

[0026] [ka]

[0027] (In the formula, R 1 each independently represents an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, or a halogen atom; n1 is an integer of 0 to 4; and each R 1 may be the same or different, and each n1 in the same or different phenylene groups may be the same or different.)

[0028] [ka]

[0029] (In the formula, R 2 each independently represents an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, or a halogen atom; n2 is an integer of 0 to 4; and each R 2 may be the same or different, and each n2 in the same or different phenylene groups may be the same or different.

[0030] R 1 and R 2The alkyl group having 1 to 10 carbon atoms in the formula (I) may be linear or branched, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, an s-butyl group, a t-butyl group, an n-hexyl group, a 2-ethylhexyl group, an n-octyl group, and an n-decyl group. R 1 and R 2 The alkyl group in the formula (I) is preferably an alkyl group having 1 to 6 carbon atoms.

[0031] R 1 and R 2 As the alkenyl group having 2 to 10 carbon atoms, R 1 and R 2 In the alkyl groups exemplified above, one in which a single bond (CC) between any two carbon atoms is replaced with a double bond (C=C), and the position of the double bond is not limited. R 1 and R 2 In the above, examples of the aryl group having 6 to 20 carbon atoms include a phenyl group, an o-tolyl group, an m-tolyl group, a p-tolyl group, a 1-naphthyl group, and a 2-naphthyl group. R 1 and R 2 In the above, examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. n1 and n2 each independently represent an integer of 0 to 4, preferably 0 to 2, and more preferably 0 to 1.

[0032] Examples of commercially available products of the compound represented by general formula (I) include Sumikaexcel PES 3600P, 4100P, and 4800P, which are trade names of Sumitomo Chemical Co., Ltd. The terminal structure of the aromatic polysulfone resin is determined according to the manufacturing method of each resin, and examples thereof include, but are not limited to, Cl, OH, and OR (R is an alkyl group).

[0033] The content of the (P) component in the total mass (100 mass%) of the resin composition for lamp members may be, for example, 50 mass% or more, 50 to 99.9 mass%, 70 to 99.5 mass%, or 80 to 99.0 mass%.

[0034] The reduced viscosity of the (P) component is preferably greater than 0.36 (dL / g) and equal to or less than 0.50 (dL / g), more preferably equal to or greater than 0.38 (dL / g) and equal to or less than 0.48 (dL / g), and even more preferably equal to or greater than 0.40 (dL / g) and equal to or less than 0.45 (dL / g). By having the reduced viscosity of the (P) component exceeding or equal to the lower limit, the occurrence of fogging in the lamp is more effectively prevented, and the heat resistance of the resin composition for lamp components is improved. By having the reduced viscosity of the (P) component equal to or less than the upper limit, the handling and moldability of the resin composition for lamp components can be improved.

[0035] The reduced viscosity of component (P) can be measured by the following method. (P) The viscosity (η) of 1 dL of a solution obtained by dissolving 1 g of component in N,N-dimethylformamide is measured at 25°C using an Ostwald-type viscosity tube. In addition, the viscosity (η0) of the solvent, N,N-dimethylformamide, is measured at 25°C using an Ostwald type viscosity tube. The specific viscosity ((η-η0) / η0) is calculated from the viscosity of the solution (η) and the viscosity of the solvent (η0). The reduced viscosity (dL / g) is calculated by dividing the specific viscosity by the concentration of the solution (approximately 1 g / dL).

[0036] The resin composition for lamp members according to the embodiment contains the component (P), which gives the composition strength suitable for use in lamp members exposed to high heat, and allows the composition to exhibit excellent heat resistance.

[0037] As an index showing the heat resistance of the resin composition for lamp components of the embodiment, the bending strength at 180° C. of the cured product of the resin composition for lamp components can be used. The bending strength at 180° C. is preferably 35 MPa or more, more preferably 40 MPa or more, even more preferably 50 MPa or more, and particularly preferably 55 MPa or more. The upper limit of the 180° C. bending strength is not particularly limited, but may be 70 MPa or less, 65 MPa or less, or 60 MPa or less. The numerical range of the above numerical value may be, for example, 35 MPa or more and 70 MPa or less, 40 MPa or more and 65 MPa or less, 50 MPa or more and 65 MPa or less, or 55 MPa or more and 60 MPa or less. The 180°C bending strength value is a value obtained by the method and measurement conditions shown below.

[0038] (180° bending strength measurement) Using the resin composition for lamp components as a molding material, an injection molding machine is used to mold rod-shaped test pieces with a width of 12.7 mm, a length of 127 mm, and a thickness of 6.4 mm at a cylinder temperature of 360°C and a mold temperature of 150°C, and a bending test is carried out in accordance with ASTM D790 at a test speed of 2 mm / min, a support distance of 100 mm, and an indenter tip radius of 5 mm to measure the bending strength at 180°C. The bending strength value is the average value of the results for three test pieces.

[0039] The glass transition temperature (°C) of the aromatic polysulfone of the embodiment is preferably 200°C or higher, and more preferably 215°C or higher. The glass transition temperature (°C) is an index for judging the degree of heat resistance of the aromatic polysulfone, and it can usually be said that the higher this temperature is, the more excellent the heat resistance is. The glass transition temperature can be calculated by a differential scanning calorimeter according to a method in accordance with JIS-K7121.

[0040] <(M) component> The component (M) contained in the resin composition for lamp members: at least one selected from the group consisting of oxides, peroxides, double oxides and carbonates of metals belonging to Group 1 or 2 of the long form periodic table will be described below.

[0041] Examples of oxides of metals belonging to Group 1 or Group 2 of the long form periodic table include those represented by the general formula M2O or M'O (in these formulas, M is a metal element belonging to Group 1, and M' is a metal element belonging to Group 2). Examples of peroxides of metals belonging to Group 1 or 2 of the long form periodic table include those represented by the general formula M'O2 (in these formulas, M is a metal element belonging to Group 1, and M' is a metal element belonging to Group 2). In the above oxides and peroxides, M is preferably at least one selected from the group consisting of Na and K. M' is preferably at least one selected from the group consisting of Mg, Ca, and Ba, more preferably at least one selected from the group consisting of Mg and Ca, and even more preferably Mg.

[0042] Examples of double oxides containing a metal belonging to Group 1 or 2 of the long periodic table include those represented by the general formula MO·mM''O2·xH2O, M'O·mM''O2·xH2O, MO·pM''2O3·mM''O2·xH2O or MO·pM'OmM'''2O3·nM''O2·xH2O (in these formulas, M is a metal element belonging to Group 1, M' is a metal element belonging to Group 2, M'' is a tetravalent metal element, M''' is a trivalent metal element, p, m and n are positive numbers of 1 or more, and x is a positive number of 0 or more). In the above-mentioned double oxide, M is preferably K, and M' is preferably at least one selected from the group consisting of Mg, Ca, and Ba. Examples of such elements include, but are not limited to, wollastonite, attapulgite, sericite, mica, potassium titanate, and barium titanate.

[0043] The carbonates containing metals belonging to Group 1 or Group 2 in the long-period type periodic table can include those represented by the general formulas M2CO3, M’CO3 or M’·M’’(CO3)2 (wherein M belongs to Group 1, and M’ and M’’ are metal elements belonging to Group 2). In the above carbonates, M is preferably K, and M’ and M’’ are preferably at least one selected from the group consisting of Mg, Ca, and Ba. Examples of these include, but are not limited to, potassium carbonate, calcium carbonate, dolomite, etc. In addition, layered double hydroxides can be exemplified as the carbonates containing metals belonging to Group 1 or Group 2 in the long-period type periodic table. Examples of the layered double hydroxides include hydrotalcite. These can be used alone or in combination of two or more. Among these, hydrotalcite is preferred. Incidentally, hydrotalcite has the formula: Mg 1-y Al y (OH)2(CO3) y / 2 ·qH2O [wherein, the numerical values of 0 < y ≦ 0.5, 0 ≦ q are represented] and is represented by this. Hydrotalcite may be a natural product or a synthetic product, and can be used regardless of its crystal structure, crystal particle size, etc.

[0044] A mixture or solid solution of the oxide, peroxide, double oxide, or carbonate of a metal belonging to Group 1 or Group 2 of the long-form periodic table may be used. Examples of the mixture or solid solution of metal oxides include calcined dolomite (a mixture containing calcium oxide and magnesium oxide), calcined hydrotalcite (a solid solution of calcium oxide and aluminum oxide), etc. Commercially available examples include calcined dolomite (such as "KT" manufactured by Yoshizawa Lime Industry Co., Ltd.), calcium oxide (such as "Moistop #10" manufactured by Sankyo Seifun Co., Ltd.), magnesium oxide (such as "Kyowamag MF-150" and "Kyowamag MF-30" manufactured by Kyowa Chemical Industry Co., Ltd., and "Puremag FNMG" manufactured by Tateho Chemical Industry Co., Ltd.), light-burned magnesium oxide (such as "#500", "#1000", and "#5000" manufactured by Tateho Chemical Industry Co., Ltd.), calcined hydrotalcite (such as "N41S" manufactured by Toda Kogyo Co., Ltd., and "KW-2100" and "KW-2200" manufactured by Kyowa Chemical Industry Co., Ltd.), and semi-calcined hydrotalcite (such as "DHT-4C" and "DHT-4A-2" manufactured by Kyowa Chemical Industry Co., Ltd.).

[0045] As the (M) component, from the viewpoint of neutralization with acidic gases (sulfur dioxide gas), those exhibiting alkalinity are preferred. For example, magnesium oxide, calcium oxide, barium oxide, barium peroxide, wollastonite, attapulgite, sericite, mica, potassium titanate, barium titanate, potassium carbonate, calcium carbonate, dolomite, hydrotalcite, calcined hydrotalcite, etc. are preferred.

[0046] The component (M) may be contained as a single type, or as a combination of two or more types.

[0047] Of the above examples, from the viewpoint of being able to more effectively reduce the occurrence of fogging in the lamp, it is preferable that the (M) component be an oxide of a metal belonging to Group 1 or 2 of the long form periodic table, and it is more preferable that the (M) component be magnesium oxide.

[0048] The content of the (M) component is preferably 0.5 to 10 parts by mass, more preferably 0.7 to 10 parts by mass, more preferably 1 to 7 parts by mass, even more preferably 1 to 5 parts by mass, and particularly preferably 1.5 to 4 parts by mass, relative to 100 parts by mass of the (P) component. The upper and lower limits of the numerical ranges of the content of the (M) component exemplified above can be freely combined. A resin composition for lamp components containing the (M) component at or above the lower limit can more effectively reduce the occurrence of fogging in lamps. Also, by containing the (M) component at or below the upper limit, the heat resistance of the composition for lamp components is good, and the melt viscosity of the resin composition for lamp components is unlikely to increase due to the addition of the (M) component, making it easier to stabilize the quality of the resin composition for lamp components.

[0049] The melt viscosity of the resin composition for lamp members is measured at 380° C. using a capillary rheometer, and can be measured by the measurement method described below.

[0050] (Measurement of apparent melt viscosity of resin composition for lamp components) The melt viscosity of the resin composition for lamp components at 380°C is measured using a capillary rheometer. The capillary has a diameter of 1.0 mm and a length of 10 mm. 20 g of the resin composition for lamp components in pellet form, which has been dried at 150°C for 4 hours, is placed in a cylinder set at 380°C, and the melt viscosity is measured at a shear rate of 12,000 s in accordance with ISO 11443. -1 The melt viscosity at this temperature is measured.

[0051] The inventors have found that the suppression of the increase in melt viscosity is more remarkable as the content of chlorine (Cl) contained in the resin composition for lamp members is higher, and in an aromatic polysulfone composition having a chlorine (Cl) content of more than 2000 mass ppm, preferably 3000 mass ppm or more and 5000 mass ppm or less, the content of the (M) component is preferably 0.5 to 10 mass parts, more preferably 0.7 to 10 mass parts, more preferably 1 to 7 mass parts, even more preferably 1 to 5 mass parts, and particularly preferably 1.5 to 4 mass parts, relative to 100 mass parts of the (P) component. The upper and lower limits of the numerical range of the content of the (M) component exemplified above can be freely combined.

[0052] Alternatively, from the viewpoint of preventing the increase in melt viscosity, the content of chlorine (Cl) contained in the resin composition for lamp members is preferably 2000 mass ppm or less, more preferably 1700 mass ppm or less, and even more preferably 1500 mass ppm or less. The lower limit of the content of chlorine (Cl) contained in the resin composition for lamp members here may be, for example, 100 mass ppm or more, or 500 ppm or more. The preferred range of the content of chlorine (Cl) contained in the resin composition for lamp members here may be, for example, 100 mass ppm or more to 2000 mass ppm or less, 100 mass ppm or more to 1700 mass ppm or less, or 500 ppm or more to 1500 mass ppm or less.

[0053] The chlorine (Cl) contained in the resin composition for lamp members may correspond to the Cl atom that the aromatic polysulfone has at its terminal.

[0054] Aromatic polysulfones are usually produced by polycondensation reaction of an aromatic dihalogenosulfone compound with an aromatic dihydroxy compound in the presence of a base and a reaction solvent (see, for example, JP-A No. 2012-509375). In other words, the aromatic polysulfone obtained by polycondensation reaction of an aromatic dihalogenosulfone compound with an aromatic dihydroxy compound has a halogen atom or a phenolic hydroxyl group at its terminal.

[0055] The content of chlorine (Cl) contained in the resin composition for lamp members can be adjusted, for example, by adopting the method disclosed in JP 2018-070698 A.

[0056] More specifically, in a method for producing an aromatic polysulfone by a polycondensation reaction between an aromatic dihalogenosulfone compound and an aromatic dihydroxy compound, the polycondensation reaction is carried out in the presence of at least one aromatic end-capping agent.

[0057] Examples of aromatic end capping agents include those disclosed in JP 2018-070698 A. For example, 4-phenylphenol, 1-naphthol, 2-naphthol, and 4-phenoxyphenol are preferred from the viewpoints of not containing a structure that is reactive to halogen atoms or prone to generating radicals, and of being easily available.

[0058] The polycondensation reaction is carried out in the presence of at least one aromatic end-capping agent to obtain aromatic polysulfone, and then the solvent is removed, or the precipitate containing aromatic polysulfone is repeatedly washed with a poor solvent, whereby chlorine (Cl) can be efficiently removed.

[0059] As shown in the examples below, the inventors have found that by using magnesium oxide as component (M), the above-mentioned increase in melt viscosity is unlikely to occur. This is probably because, while the addition of a metal oxide may cause a polymerization reaction of aromatic polysulfone having Cl atoms at its terminals to proceed, the use of magnesium oxide makes it difficult for such polymerization reactions to proceed.

[0060] Therefore, from the standpoint of being able to particularly effectively reduce the occurrence of fogging in the lamp and further being less likely to cause the above-mentioned increase in melt viscosity, it is particularly preferred that the component (M) is magnesium oxide. Since ramp components are often relatively large, the composition is often required to have a suitable flowability when molding them. The fact that the melt viscosity of the resin composition for ramp components according to the embodiment is unlikely to increase is a suitable feature for a composition used in the manufacture of ramp components. Also, from the viewpoint of suppressing an increase in melt viscosity, it is preferable that the content of the (M) component is within the range exemplified above.

[0061] In the resin composition for lamp components of the embodiment, the reduced viscosity of the (P) component is more than 0.36 (dL / g) and not more than 0.50 (dL / g), and the (M) component is magnesium oxide, which is preferable because it further improves the heat resistance of the resin composition for lamp components and further reduces the occurrence of fogging in the lamp.

[0062] In the resin composition for lamp components of the embodiment, the reduced viscosity of the (P) component is more than 0.36 (dL / g) and is not more than 0.50 (dL / g), the (M) component is magnesium oxide, and the content of the (M) component is 1 to 10 parts by mass per 100 parts by mass of the (P) component, which is particularly preferred because this further improves the heat resistance of the resin composition for lamp components and reduces the occurrence of fogging in the lamp.

[0063] (Other ingredients) In this embodiment, the resin composition for lamp members may contain other components that do not fall under either the component (P) or the component (M) as long as the effects of the present invention are not impaired.

[0064] Examples of other components include fillers, additives, and resins other than the component (P) (hereinafter sometimes referred to as "other resins"). One type of these other components may be contained alone, or two or more types may be contained.

[0065] The filler may be a fibrous or particulate filler. The filler may be an inorganic filler or an organic filler.

[0066] Examples of fibrous inorganic fillers include glass fibers, carbon fibers such as bread-based carbon fibers and pitch-based carbon fibers, ceramic fibers such as silica fibers, alumina fibers, and silica-alumina fibers, and metal fibers such as stainless steel fibers. In addition, whiskers such as potassium titanate whiskers, barium titanate whiskers, wollastonite whiskers, aluminum borate whiskers, silicon nitride whiskers, and silicon carbide whiskers can also be mentioned.

[0067] Examples of glass fibers include chopped glass fibers, milled glass fibers, and the like, which are produced by various methods.

[0068] Examples of carbon fibers include bread-based carbon fibers made from polyacrylonitrile, pitch-based carbon fibers made from coal tar or petroleum pitch, cellulose-based carbon fibers made from viscose rayon or cellulose acetate, etc., and vapor-grown carbon fibers made from hydrocarbons, etc. The carbon fibers may be chopped or milled.

[0069] Examples of particulate inorganic fillers include silica, alumina, titanium oxide, boron nitride, silicon carbide, and calcium carbonate.

[0070] Examples of the additives include a metering stabilizer, a mold release agent, an antioxidant, a heat stabilizer, an ultraviolet absorber, an antistatic agent, a surfactant, a flame retardant, and a colorant.

[0071] Examples of other resins include thermoplastic resins other than liquid crystal polymers, such as polypropylene, polyamide, polyester, polyphenylene sulfide, polyether ketone, polycarbonate, polyphenylene ether, polyetherimide, and fluororesin; and thermosetting resins, such as phenolic resin, epoxy resin, polyimide resin, and cyanate resin.

[0072] <<Method for producing resin composition for lamp member>> The resin composition for lamp members of this embodiment can be produced by mixing the component (P), the component (M), and other components used as necessary all at once or in a suitable order. The method for producing a resin composition for lamp members of this embodiment includes a step of mixing the component (P) and the component (M).

[0073] Examples of the component (P) and the component (M) include those described above in the section "Resin composition for lamp members."

[0074] The amount of the (M) component used is preferably 0.5 to 10 parts by mass, more preferably 1 to 7 parts by mass, and even more preferably 1.5 to 4 parts by mass, per 100 parts by mass of the (P) component. A resin composition for lamp components obtained by mixing the (M) component at a ratio equal to or greater than the above lower limit can more effectively reduce the occurrence of fogging in lamps. Furthermore, a resin composition for lamp components obtained by mixing the (M) component at a ratio equal to or less than the above upper limit has good heat resistance, is less susceptible to an increase in melt viscosity due to the addition of the (M) component, and is easy to stabilize the quality of the resin composition for lamp components.

[0075] The mixing is preferably performed by melt kneading. The resin composition for lamp members of the present embodiment can be provided as pellets obtained by melt kneading the (P) component, the (M) component, and other components used as needed using an extruder.

[0076] The resin composition for lamp components of the embodiment contains component (M): at least one selected from the group consisting of oxides, peroxides, double oxides, and carbonates of metals belonging to Group 1 or 2 of the long form periodic table, thereby exerting an effect of reducing fogging of the lamp.

[0077] The effect of reducing the fogging of a lamp in the resin composition for lamp components can be confirmed without actually manufacturing a lamp. For example, as in the method specifically described in the examples, a test device simulating a lamp can be used, and a cured product of the resin composition for lamp components can be placed in a container that assumes the spatial volume of a housing that houses a light source, and then the inside of the container can be heated to obtain a comparison result of the amount of components attached to the inside of the container before and after heating, and a comparison result of the actual degree of fogging. Then, compared to the resin composition containing the (P) component, the resin composition according to the embodiment obtained by further adding the (M) component to the resin composition has a reduced amount of components attached to the inside of the container after heating, and when the degree of fogging is low or the heating time until fogging occurs is short, it can be determined that the effect of reducing the fogging of a lamp has been achieved.

[0078] The mechanism by which component (M) exerts its effect of reducing lamp fogging is believed to be as follows. When component (P) contained in the resin composition for lamp components is heated, sulfurous acid (SO2) gas is generated, and it is believed that, for example, sodium sulfate reacts with Na contained in the glass lens of the lamp and adheres to the glass lens. It is believed that by adding component (M) to this, component (M) reacts with sulfurous acid gas, suppressing the generation of sulfurous acid gas.

[0079] As described above, the resin composition for lamp components of the embodiment contains the component (P), so that the molded article molded from the composition for lamps of the embodiment exhibits excellent heat resistance. Also, the resin composition for lamp components of the embodiment contains the component (M), so that the occurrence of fogging in the lamp molded from the composition can be reduced. Furthermore, when the reduced viscosity of component (P) exceeds 0.36 (dL / g), the effect of reducing the occurrence of fogging in the lamp is further enhanced and more suitable heat resistance properties are exhibited for use as a lamp component. When the reduced viscosity of component (P) is 0.50 (dL / g) or less, the molding properties for molding the lamp component are improved. Furthermore, by using magnesium oxide as component (M), the effect of reducing the occurrence of fogging in the lamp is further enhanced, and the molding characteristics for molding the lamp components are also improved. As described above, the lamp composition of the embodiment has extremely excellent properties as a composition used for molding lamp components. EXAMPLES

[0080] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples.

[0081] Evaluation <Measurement of reduced viscosity of aromatic polysulfone> 1 g of the aromatic polysulfone to be measured was dissolved in N,N-dimethylformamide to a volume of 1 dL, and the viscosity (η) of this solution was measured at 25° C. using an Ostwald-type viscosity tube. The viscosity (η0) of the solvent N,N-dimethylformamide was also measured at 25° C. using an Ostwald-type viscosity tube. The specific viscosity ((η-η0) / η0) was calculated from the viscosity (η) of the solution and the viscosity (η0) of the solvent, and the reduced viscosity (dL / g) of the resin was calculated by dividing the specific viscosity by the concentration of the solution (approximately 1 g / dL).

[0082] <Cloudy Test> Pellets of the resin composition for lamp components were molded into flat plate-shaped test pieces with a width of 64 mm, a length of 64 mm, and a thickness of 1 mm using an injection molding machine (PS40E5ASE, Nissei Plastics Co., Ltd.) at a cylinder temperature of 360°C and a mold temperature of 150°C, and then cut into 10 mm squares to serve as test pieces. 2 g of the test piece was placed in a petri dish with a diameter of 32 mm and a height of 15 mm, and soda-lime glass was placed on the petri dish and heated on a hot plate set at 260°C, and the time until fogging occurred on the glass was measured. The longer this time, the more reduced the fogging.

[0083] <Measurement of 180°C bending strength> Pellets of the resin composition for lamp components were molded into rod-shaped test pieces with a width of 12.7 mm, a length of 127 mm, and a thickness of 6.4 mm using an injection molding machine (PS40E5ASE, Nissei Plastic Industrial Co., Ltd.) at a cylinder temperature of 360°C and a mold temperature of 150°C. A bending test was carried out in accordance with ASTM D790 at a test speed of 2 mm / min, a support distance of 100 mm, and an indenter tip radius of 5 mm to measure the bending strength at 180°C. The bending strength value was the average value of the results for three test pieces.

[0084] <Measurement of apparent melt viscosity of resin composition for lamp members> The melt viscosity of the resin composition for lamp members was measured at 380°C using a capillary rheometer. A capillary of 1.0 mm diameter x 10 mm was used, and 20 g of pellets of the resin composition for lamp members dried at 150°C for 4 hours were placed in a cylinder set at 380°C, and the melt viscosity was measured at a shear rate of 12000 s in accordance with ISO 11443. -1 The melt viscosity at 100° C. was measured.

[0085] <Measurement of glass transition temperature of aromatic polysulfone> The glass transition temperature was calculated using a differential scanning calorimeter (Shimadzu DSC-50) according to the method of JIS-K7121. Approximately 10 mg of the sample was weighed out and heated to 400°C at a heating rate of 10°C / min, then cooled to 50°C, and heated again to 400°C at a heating rate of 10°C / min. The glass transition temperature was calculated from the DSC chart obtained from the second heating according to the method of JIS-K7121.

[0086] <Production of resin composition for lamp components> Example 1 (Reference example) As the (P) component, 100 parts by mass of Sumikaexcel PES4100P (polyethersulfone (PES), manufactured by Sumitomo Chemical Co., Ltd., glass transition temperature: 225°C, reduced viscosity: 0.41 dL / g) and as the (M) component, magnesium oxide (Kyowamag 150 manufactured by Kyowa Chemical Industry Co., Ltd.) were used. 0 After mixing with 0.5 parts by mass, pellets of the resin composition for lamp members were produced by melt-kneading using a twin-screw extruder (PCM-30, manufactured by Ikegai Iron Works Co., Ltd.) The melt-kneading conditions were a cylinder setting temperature of 340°C and a screw rotation speed of 150 rpm.

[0087] (Examples 2 to 12, Comparative Examples 1 to 2) (Examples 5 to 7 and 10 to 12 are reference examples) Pellets of a resin composition for lamp components were produced in the same manner as in Example 1, except that the type of PES, the type of metal oxide, and the blending amount thereof were changed as shown in Table 1. In the table, "-" means that the component was not included. Calcium oxide was used (VESTA-PP) manufactured by Inoue Sekiryo Kogyo Co., Ltd. Sumikaexcel PES3600P was polyethersulfone (PES), manufactured by Sumitomo Chemical Co., Ltd., glass transition temperature: 225°C, reduced viscosity: 0.36 dL / g.

[0088] The test pieces (molded articles) of each produced resin composition for lamp members were subjected to the above-mentioned fogging test and measurement of bending strength at 180° C. The results are shown in Table 1.

[0089] The above-mentioned apparent melt viscosity was also measured for the resin compositions for lamp members of Comparative Example 1, Example 1, Example 2, Example 5, and Example 6. The results are shown in FIG.

[0090] [Table 1]

[0091] Referring to Table 1, the resin compositions for lamp components of Examples 1 to 10, which contained the (P) component and the (M) component, showed reduced fogging in the fogging test compared to the resin compositions for lamp components of Comparative Examples 1 and 2, which did not contain the (M) component.

[0092] Furthermore, the resin compositions for lamp members of Examples 1 to 7 in which the reduced viscosity of the PES component (P) exceeded 0.36 (dL / g) had high flexural strength at 180° C. and particularly excellent heat resistance.

[0093] Furthermore, comparisons between Example 2 and Example 8, between Example 4 and Example 9, between Example 5 and Example 10, between Example 6 and Example 11, and between Example 7 and Example 12 show that the higher the reduced viscosity of the PES of component (P), the more suppressed the occurrence of fogging in the fogging test.

[0094] Furthermore, comparing Example 2 with Example 6, and comparing Example 4 with Example 7, it was found that the use of MgO as the (M) component suppressed the occurrence of fogging in the fogging test more than the use of CaO as the (M) component.

[0095] In Examples 2 to 4, in which the reduced viscosity of the PES component (P) exceeded 0.36 (dL / g) and MgO was used as the component (M), the occurrence of fogging in the fogging test was particularly suppressed.

[0096] Furthermore, referring to FIG. 2, it was also found that in Examples 1 and 2 in which MgO was used as the (M) component, the melt viscosity of the composition was less likely to increase than in Examples 5 and 6 in which CaO was used as the (M) component.

[0097] The configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited to each embodiment, but is limited only by the scope of the claims. [Explanation of symbols]

[0098] 1...lamp, 3...lamp member, 10...reflector, 12...light source, 14...lens, 20...lens holder

Claims

1. Component (P): aromatic polysulfone, (M) component: magnesium oxide, Contains The resin composition for lamp members has a content of the (M) component of 0.7 to 10 parts by mass per 100 parts by mass of the (P) component.

2. 2. The resin composition for lamp members according to claim 1, wherein the reduced viscosity of the component (P) is more than 0.36 (dL / g) and 0.50 (dL / g) or less.

3. 3. The resin composition for lamp members according to claim 1, wherein the content of the (P) component is 50 to 99.0 mass% in the total mass (100 mass%) of the resin composition for lamp members.

4. A lamp member molded from the resin composition for lamp members according to any one of claims 1 to 3.

5. Component (P): aromatic polysulfone, (M) component: magnesium oxide, Mixing the above components, The (M) component is mixed in an amount of 0.7 to 10 parts by mass per 100 parts by mass of the (P) component.

Citation Information

Patent Citations

  • Automobile lamp shade molding material and preparation method thereof

    CN106810804A

  • Lamp reflector

    JP1999096817A

  • Resin composition

    JP2003301107A

  • Reflector

    JP2004045883A

  • Molding material containing polyaryl ether with improved surface quality

    JP2010530914A